Intrafamilial transmission of hepatitis C virus infection - Ali HAFTA; Salih ÇOLAKOĞLU; Ender SERİN and Fügen YARKIN and Hikmet AKKIZ and Yılmaz ERGÜN and Macit SANDIKÇI and Fatih KÖKSAL and İsmail ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-